Technological features of production and quality characteristics of restructured poultry ham with lentil isolate - I. Simonova; U. Drachuk; B. Halukh; І. Basarab; О. Moroz; H. Koval; Y.-I. Hordynska (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького. Серія: Харчові технології)
The article presents the results of research on the technological aspects of producing restructured hams from poultry meat, specifically samples “Chicken Ham” No. 1 and “Turkey Ham” No. 2. The primary objective was to determine the impact of raw material composition and technological parameters on the physicochemical, functional-technological, and organoleptic properties of the final products. The recipe included lentil isolate, starch, mechanically deboned meat (MDM) from chicken and turkey, as well as auxiliary ingredients: salt, coloring agent, sodium tripolyphosphate, sodium nitrite, pepper, and nutmeg. The study found that active acidity (pH) significantly affects the water-binding capacity of the meat mixtures. Sample No. 1 had a 1.6 % higher pH level compared to sample No. 2 and the control, which resulted in lower water- and fat-binding capacities. Meanwhile, sample No. 2 demonstrated the best yield (93.9 %) and the lowest mass loss (6.1 %), indicating the effectiveness of using turkey meat in the formulation. The research also showed an increase in the protein content by 32.44 % (No. 1) and 36.48 % (No. 2) compared to the control. Organoleptic evaluation confirmed the high taste quality of the products, making them suitable for market implementation. Microbiological studies confirmed that the products meet the requirements of regulatory documentation. The results of functional-technological indicators confirmed that sample No. 1 had a higher fat-binding capacity, while sample No. 2 exhibited better moisture retention and product yield. The yield and loss calculations for the restructured hams revealed that sample No. 2 had the highest yield (93.9 %) and the lowest losses (6.1 %), while sample No. 1 showed slightly lower values (90.04 % yield and 9.96 % losses). The study also demonstrated that lentil isolate used in the formulation positively influenced the product yield and its moisture retention ability. Sample No. 1, which contained more starch and lentil isolate, showed a higher moisture retention level but was inferior to sample No. 2 in fat-binding capacity. This suggests that recipe modifications, such as the use of different meat types and auxiliary components, have a decisive impact on the functional-technological characteristics of the hams. Additionally, significant attention was given to the microbiological safety of the test samples, as the production process for hams involves thermal processing. The results of microbiological analysis confirmed that all samples met established regulatory requirements, indicating the safety of production and the feasibility of applying this technology in industrial settings.